Sedimentation process and design of settling systems - De, Alak (Springer, 2017)
This book is designed to serve as a comprehensive source of information of sedimentation processes and design of settling systems, especially as applied to design of such systems in civil and environmental engineering. The book begins with an introduction to sedimentation as a whole and goes on to cover the development and details of various settling theories. The book traces the chronological developments of the comprehensive knowledge of settling studies and design of settling systems from 1889.A new concept of 'Velocity Profile Theorem', tool for settling problem analysis, has been employed to the analysis of the phenomenon of short circuiting. Complete theory of tube settling has been developed and its application to the computation of residual solids from the assorted solids through the same has been demonstrated. Experimental verification of the tube settling theory has also been presented. Field-oriented compatible design and operation methodology of settling system has been developed from the detailed study of a real settling system. New parameter for settling performance comparison appears to do justice for its purpose. Design methodology of high rate settling systems has been presented with worked out examples and the flexibility of control of operation has been shown. Lastly, along with the presentation of all the theories of 'Thickener Design' the same problem of thickening has been solved with all the methods to reveal the variation in the designed thickeners. The contents of this book will be useful to students, researchers, and professional engineers alike.
Keywords: Sedimentation and deposition.; elektronické knihy; electronic books